Rigid ureteroscopic lithotripsy versus percutaneous nephrolithotomy for large proximal ureteral stones: A meta-analysis. - Qing Wang; Jiachao Guo; Henglong Hu; Yuchao Lu; Jiaqiao Zhang; Baolong Qin; Yufeng Wang; Zongbiao Zhang; Shaogang Wang (PLoS ONE, 2017)
OBJECT:To compare the safety and efficacy of rigid ureteroscopic lithotripsy (rigid URSL) and percutaneous nephrolithotomy (PCNL) in treating large proximal ureteral stones. METHODS:A systematic search of PubMed, EMBASE, Cochrane Library, and Web of Science databases was performed to find out relevant studies. After literature screening according to the predetermined inclusion and exclusion criteria, data of eligible studies was extracted and then a meta-analysis was conducted via RevMan 5.3 software. RESULTS:Five randomized controlled trials (RCTs), one prospective and four retrospective cohort studies involving 837 patients were included. Patients underwent rigid URSL were associated with shorter operation time (WMD, -23.66min; 95%CI, -45.00 to -2.32; p = 0.03), shorter hospital stay (WMD, -2.76d; 95%CI, -3.51 to -2.02; p< 0.00001), lower 3rd-day (RR, 0.73; 95%CI, 0.66 to 0.82; p < 0.00001) and 1st-month (RR, 0.82; 95%CI, 0.77 to 0.87; p < 0.00001) stone-free rate, higher risk of conversion to other surgical procedures (RR, 4.28; 95%CI, 1.93 to 9.46; p = 0.0003), higher incidence of migration (RR, 28.49; 95%CI, 9.12 to 89.00; p < 0.00001) and ureteral perforation (RR, 6.06; 95%CI, 1.80 to 20.44; p = 0.004), lower risk of fever (RR, 0.64; 95%CI, 0.42 to 0.97; p = 0.04), transfusion (RR, 0.19; 95%CI, 0.04 to 0.85; p = 0.03) and hematuria (RR, 0.38; 95%CI, 0.25 to 0.57; p < 0.0001). No significant difference was observed in terms of incidence of embolization, pain and ureterostenosis. When cohort studies or studies in which flexible ureteroscopy was used as an intraoperative auxiliary procedure were excluded, we both found that most of the results kept stable. CONCLUSIONS:Both PCNL and rigid URSL are safe for patients with large proximal ureteral stones while PCNL is more effective in stone clearance.